(untitled) - Diarraáouba, N.=700 1 N'Gueáan, A.; Edmont, K.
(Es, En, Pt)
ilus., 15 ref.
Keywords: BUTYROSPERMUM PARADOXUM; TAXONOMIA; ARBOLES DE PROPOSITO MULTIPLE; NOTICIARIO DE RECURSOS FITOGENETICOS